AB1123 Lean (LM) and Fat Appendicular (FM) Mass in Late (LOA) VS Early Knee Osteoarthritis (EOA) Measured by Electrical Bioimpedance Analysis (BIA); What's the Role of Body Composition Phenotype in These Patients?. (9th June 2015) - Valerio, I.A.; Sanchez, A.; Espinosa, R.; Evia, A.N.; Ilizaliturri, V.M.; Pabelto, P.; Hernandez, A.; Hernandez, L.
Abstract : Background: Total body fat mass is related to development of knee OA (KOA), strength and lean body mass of quadriceps in the setting of neutral articular alignment is a risk factor for loss of articular space in KOA and further incapacity. Higher percentage of body fat mass has been established as a risk factor for postoperative complications as transfusion requirement and longer in-hospital stay; progressive loss of lean mass precludes poor funtional and mortality outcomes in elderly (sarcopenia), however its relationship with functional outcomes in younger patients with E/L-OA remains unknown. Objectives: To describe differences in body composition phenotypes measured as total and appendicular lean/fat body mass between early vs late KOA cohort patients and its relationship with quality of life and functional outcomes. Methods: We conducted a cross-sectional, observational study. Patients must full-fill ACR Knee primary OA criteria, autoimmune and secondary OA were excluded. Kellgren & Lawrence score less than or equal to II where classified as EOA, and patients full filling criteria for knee arthroplasty were classified as LOA. A protocolized interview collected epidemiological data, joint function with WOMAC and other knee index; Patients were analyzed with multifrequency BIA (InBody 720®) to determine FM and LM. Analysis: Appropriate descriptive and bivariate test compared data between EOA vs. LOA. Results: 110 patients were evaluated, 56 with EOA and 54 LOA. The EAO group was younger: 48.5 vs. 65.5 y.o (p=0.001). Proportion of women was superior in both groups: 71.8% women. The OA evolution was 20.3 months in EOA vs 60 months in LOA (p=0.001). Main comparisons are shown in table 1 . Conclusions: We found remarkable differences in total and appendicular LM and BM in EOA vs LOA, Sarcopenic Obesity (predominant higher fat mass than lean mass) body composition phenotype is probably the most prevalent in both groups but with more functional impairment in LOA, even when BMI where not significantly different between groups. As a limitantion we lack of reference body composition normal population values to compare with. However we propose that good/poor outcomes after total knee arthroplasty might be related to proportion of total and appendicular preoperative lean mass/fat mass relationship; it could be a target of treatment in EOA and LOA patients, further research is needed in this field. References: Sowers, M. F. et al. BMI vs body composition and radiographically defined osteoarthritis of the knee in women: a 4-year follow-up study. Osteoarthritis Cartilage 16, 367–372 (2008). Sharma, L., Dunlop, D. D., Cahue, S., Song, J. & Hayes, K. W. Quadriceps strength and osteoarthritis progression in malaligned and lax knees. Ann. Intern. Med. 138, 613–619 (2003). Lee, S., Kim, T.-N. and Kim, S.-H. (2012), Sarcopenic obesity is more closely associated with knee osteoarthritis than is nonsarcopenic obesity: A cross-sectional study. Arthritis & Rheumatism, 64: 3947–3954. doi: 10.1002/art.37696. Ledford, Cameron K. et al. Percent Body Fat More Associated with Perioperative Risks After Total Joint Arthroplasty Than Body Mass Index. The Journal of Arthroplasty, 29(9):150 - 154. Disclosure of Interest: None declared